2008
DOI: 10.1248/bpb.31.2073
|View full text |Cite
|
Sign up to set email alerts
|

Corynoxeine Isolated from the Hook of Uncaria rhynchophylla Inhibits Rat Aortic Vascular Smooth Muscle Cell Proliferation through the Blocking of Extracellular Signal Regulated Kinase 1/2 Phosphorylation

Abstract: The proliferation of vascular smooth muscle cells (VSMCs) induced by injury to the intima of arteries is an important etiologic factor in vascular proliferative disorders such as atherosclerosis and restenosis. Uncaria rhynchophylla is traditional Chinese herb that has been applied to the treatment of convulsive disorders, such as epilepsy, in China. In the present study, we examined whether corynoxeine exerts inhibitory effects on plateletderived growth factor (PDGF)-BB-induced rat aortic VSMC proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The results of our study showed that Ang II increased phosphorylation of ERK1/2 and stimulated cellular proliferation; in contrast, the ERK inhibitor PD98095 blocked Ang II-induced ERK1/2 phosphorylation and significantly inhibited Ang II-induced HUVSMC proliferation, indicating that ERK1/2 activation works in parallel with HUVSMC proliferation. These results are in line with EI Mabrouk et al and are also supported by another study in which VSMC proliferation induced by PDGF was inhibited by corynoxeine through the blocking of ERK1/2 phosphorylation [21,36] . Therefore, the present data confirm that activation of ERK1/2 plays an important part in HUVSMC proliferation induced by mitogens, such as Ang II.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study showed that Ang II increased phosphorylation of ERK1/2 and stimulated cellular proliferation; in contrast, the ERK inhibitor PD98095 blocked Ang II-induced ERK1/2 phosphorylation and significantly inhibited Ang II-induced HUVSMC proliferation, indicating that ERK1/2 activation works in parallel with HUVSMC proliferation. These results are in line with EI Mabrouk et al and are also supported by another study in which VSMC proliferation induced by PDGF was inhibited by corynoxeine through the blocking of ERK1/2 phosphorylation [21,36] . Therefore, the present data confirm that activation of ERK1/2 plays an important part in HUVSMC proliferation induced by mitogens, such as Ang II.…”
Section: Discussionsupporting
confidence: 91%
“…other herbs to minimize the conversion of active components (Wu, 1958;. Recently, the aqueous extract of U. rhynchophylla have been reported in the treatment of hypertension, cancer and neurological disorders (epilepsy, Alzheimer's disease, etc) (Fujiwara et al, 2006;Kim et al, 2008;Lee, 2000;Lee et al, 2003;Suk et al, 2002).…”
Section: Medicinal Usesmentioning
confidence: 99%
“…The differential actions on ERK1/2 and AKT have been reported previously. For example, corynoxeine from the Chinese herb (Kim et al, 2008) or knockdown of nonreceptor tyrosine kinase Abl (Jia et al, 2012) attenuated PDGFinduced ERK1/2 phosphorylation but not AKT. In contrast, nitric oxide (Sandirasegarane et al, 2000) as well as bioflavonoids such as tangeretin (Seo et al, 2011), quercetin (Ishizawa et al, 2009), or cudraflavanone (Han et al, 2007), inhibit PGDF-BB-induced SMC proliferation and migration by blocking AKT but not ERK1/2 activation.…”
Section: Vinpocetine Inhibits Pathological Vascular Remodeling 485mentioning
confidence: 99%